2015
DOI: 10.1007/s00296-015-3349-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of computer-based analysis using temporal subtraction to assess joint space narrowing progression in rheumatoid patients

Abstract: Our computer-based method can detect the chronological change in joint space width between baseline and follow-up images as the joint space difference index (JSDI). The aim of this study was to verify the sensitivity and specificity of our computer-based method in assessment of joint space narrowing progression in rheumatoid patients. Twenty-seven patients (24 women and 3 men) with rheumatoid arthritis underwent radiography of the bilateral hand at baseline and at 1 year. The joint space narrowing (JSN) of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…They confirmed that when the SHS score increased between baseline and follow-up images, the JSDI tended to demonstrate higher values [11]. However, this computer-based method has not been fully validated in terms of reliability; it includes subjective manual aspects such as ROI setting and image superimposing.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…They confirmed that when the SHS score increased between baseline and follow-up images, the JSDI tended to demonstrate higher values [11]. However, this computer-based method has not been fully validated in terms of reliability; it includes subjective manual aspects such as ROI setting and image superimposing.…”
Section: Introductionmentioning
confidence: 57%
“…We have developed a computer-based method for the assessment of joint space width difference which can objectively detect slight JSN between two images and compute the joint space difference index (JSDI) using a temporal subtraction technique [10,11]. This method allows the objective and quantitative assessment of JSN progression in patients with RA with high sensitivity and specificity [10,11], using a conventional scoring method as the standard of reference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A portion of our patient population has been previously reported. 15 The study was conducted in accordance with the Declaration of Helsinki and was approved by the local ethics committee. Informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Although a previous study 15 showed the relatively high sensitivity and specificity of the computer-based method for JSN progression in carpal joints as well as finger joints, it is unclear whether our computer-based method can quantify the JSN progression as well as the Sharp/van der Heijde (SvdH) method in carpal joints. Our aim in this study was to investigate the validity of our computer-based method in rheumatoid wrists.…”
Section: Introductionmentioning
confidence: 99%